Does digital marketing really boost city tourism? Evidences from Porto’s experience - Castro, Sandra Raquel (2021)
Purpose: This article analyses the digital marketing strategy of Porto City, aiming at providing a theoretical and practical contribution on the importance of digital marketing tools to promote tourist destinations. Methodology: The current study applies the case-study methodology using two sets of data: (1) semi-structured focused interviews were carried out with tourists and key players on the promotion of Porto as tourism destination; (2) information available on the official websites of “Porto Destination” management entities. A model on Search Engine Marketing and display advertising applied to tourism is proposed. Findings: We found that these are very effective tools when it comes to attracting traffic to the destination websites, and that are likely to successfully explain the efficiency of the online promotion of a place. Another relevant result is the importance of the customization, which can be attained through the qualification of users and through the collected data on their preferences, through social networks and feedback. Originality/value: The originality of the study stems from the adoption of the theoretical determinants used, the proposed model of analysis and the different theoretical bodies from where the constructs and relations were pulled out. This way the paper provides a new way to approach the problem of marketing a touristic destination. Research limitations: Due to the difficulty to motivate tourists to participate in the interviews, the main limitation of the study is the number of interviews conducted.